Advance on Traditional Chinese Meidicine Clinical Research of Precancerous Lesions of Gastric Cancer - Zhao, Yifan; Wen, Xili (Journal of Contemporary Medical Practice, 2026)
Precancerous Lesions of Gastric Cancer (PLGC) constitute a critical stage in the development and progression of gastric carcinoma. Modern medicine lacks specific therapeutic agents for PLGC, whereas Traditional Chinese Medicine (TCM) has demonstrated advantages in improving symptoms and reversing early-stage pathological changes. By reviewing relevant literature in recent years, this paper summarizes and analyzes the current research status of TCM interventions for PLGC from six aspects: etiology and pathogenesis, pattern differentiation and classification, herbal medicine therapy, and non-pharmacological therapies. It is concluded that the disease location of PLGC is in the spleen and stomach, with spleen deficiency as the root of the core pathogenesis and qi stagnation, phlegm turbidity, stasis, and toxin as the branch manifestations. Among the pattern differentiations, the spleen-stomach deficiency pattern is the most commonly observed. Furthermore, it has been confirmed that herbal medicine, as well as non-pharmacological therapies including acupuncture, moxibustion, and acupoint application, have demonstrated definitive efficacy in improving clinical symptoms, reversing gastric mucosal pathological changes, regulating the inflammatory-immune microenvironment, and blocking the “inflammation-cancer” transformation. In the future, high-quality multicenter randomized controlled trials are needed, combined with modern omics technologies, to further elucidate their mechanisms of action.